Diverse spectrum of facial dog bite presentation and their management - Jain, Rakesh Kumar; Prakash, Gautam; Midya, Manojit; Sharma, Pankaj (International Surgery Journal, 2018)
Background: Dog bite patients are frequently encountered in our hospital seeking immediate as well as delayed reconstruction. More than two third of dog bite injuries involve head, neck and scalp region. Facial dog bites present a challenge for the surgeon, as they lead to cosmetic disfigurement and psychological trauma to the patient. Following thorough washout and debridement, we have used various reconstructive techniques for definitive management of wounds like- primary repair, V-Y advancement flap, nasolabial flap, SSG, FTG and Karapandzic flap. Purpose of the present study is to share our experiences in management of dog bite wounds on the face in both adult and paediatric patients with available reconstructive options to maximize the functional and cosmetic outcomes by using basic principles of surgery. Methods: Present study was a single centre retrospective study conducted in a tertiary care centre from February 2013 to January 2018. Total 497 patients of dog bite who presented in the emergency department were enrolled. Out of them 310 patients had involvement of head, neck and scalp requiring surgical intervention in any form. Results: In last five years, we have encountered mid face predilection in face, head and neck cases. Out of 310 cases, lip (25.16%) and cheek (24.51%) were involved in majority of the patients. Flap cover surgery is required in majority of the scalp and nose group of patients, as there is less mobility of tissue present in surrounding region, while cheek and lip were managed with primary closure in most of the patients. Conclusions: Although most of the dog bites are preventable, but cases of dog bite are increasing continuously. Child should never be left alone with dogs and, if they are fear of dogs, it’s better not to obtain dogs. As far now, it’s a major concern for treating physician or surgeon to provide optimal cosmetic as well as functional outcome. Early surgical intervention for wound management gives better results with the use of basic principles of plastic surgery.